CAPITAL MARKET DEVELOPMENTS ON INDONESIA'S ECONOMIC GROWTH IN 2019-2023: CHALLENGES AND PROSPECTS IN THE FUTURE - Putri, Diva Carrisa; Amalia As’adi, Firda Rizqi; Alfado Chievo Javantara; Moch Miqdad; Maryam Bte Badrul Munir (Journal of Management and Islamic Finance, 2024)
Indonesian society with a Muslim majority can invest using the Sharia capital market, where the Sharia capital market is an investment facility for the Muslim community based on sharia principles. Methods: The research method used is a literature study with descriptive analysis techniques by collecting data in the form of writings from previous research and arranging them to see the results of the data that has been collected, this technique does not use numbers for statistical testing or classical assumptions. Results: The Islamic capital market in Indonesia has made a significant contribution to economic growth from 2019 to 2023. This contribution is reflected in the increase in assets and capitalization of the Islamic capital market, which not only shows absolute growth but also an increase in the proportion of the national Gross Domestic Product (GDP). With consistent growth in assets and capitalization and an increase in the number of investors, the Islamic capital market plays an important role in increasing financial inclusion and national economic stability. The efforts of the government and OJK in strengthening regulations and product innovation in this sector are expected to continue to drive sustainable growth in the future.  Conclusion and suggestion: The conclusion of this study highlights that the development of sharia products, OJK regulations, and product innovation have a significant positive impact on long-term economic growth. The sharia capital market also has great potential to support long-term economic growth and financial inclusion, with the hope that strengthening regulations and innovation will continue to drive positive contributions to the national economy.